Agroholdings and clusters in Kazakhstan's agro-food sector; Agroholdings und Clusters in Kasachstan's Agrar- und Ernährungssektor - Jürgen Wandel (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2009)
The paper provides an overview of the institutional arrangements on the micro level that have evolved in the agro-food sector of Kazakhstan in the course of transition. Emphasis is laid on more complex arrangements like agroholdings and clusters, hitherto mostly unknown in the agro-food sectors of established market economies. It is shown that agroholdings are concentrated mainly in the northern part of Kazakhstan and to a large extent in the grain sector, while in the south a scattered small scale (individual) farm structure has emerged. Parallel to this market-driven development, the Kazakhstani government tries to promote other institutional arrangements that it deems to be of superior competitiveness, especially agro-food clusters. Refering to Hayek's concept of pretence of knowledge and empirical evidence of cluster facilitation policies of other countries the success of the Kazakhstani cluster initiative is questioned. – – Der Beitrag bietet einen Überblick über die institutionellen Arrangements auf Mikroebene, die sich in der Agrar- und Ernärhungswirtschaft Kasachstan im Laufe des Transformationsprozesses herausgebildet haben. Das Hauptaugenmerk liegt auf komplexere Arrangements wie Agroholdings und Clusters, die bislang in den Agrar- und Ernährungssektoren etablierter Marktwirtschaft wenig verbreitet sind. Es wird gezeigt, daß Agroholdings hauptsächlich im Norden von Kasachstan und da im Getreidesektor konzentriert sind, während im Süden zersplitterte kleinbäuerliche Strukturen vorherrschen. Parallel zu dieser aus dem Spiel der Marktkäfte heraus entstandenen Entwicklung versucht die kasachstanische Regierung andere institutionelle Arrangements zu fördern, insbesondere Clusters, von denen sie glaubt, sie besäßen eine überlegene Wettbewerbsfähigkeit. Unter Rückgriff auf Hayeks Konzept der Anmaßung von Wissen und empirische Ergebnisse von Clusterförderungspolitiken in anderen Ländern wird der Erfolg der Cluster-Initiative in Kasachstan in Frage gestellt.
urn:nbn:de:gbv:3:2-11300
Keywords: Q13; Q18; L22; 330; Agroholdings; cluster; Kazakhstan; agricultural policy; institutional change; Agroholdings; Cluster; Kasachstan; Agrarpolitik; institutioneller Wandel